Pengembangan Komoditi Unggulan Pertanian dalam Persfektif Digital Marketing di Kecamatan Ganding - Anis Kurli; Rillia Aisyah Haris; Fauzi Helmi; Hidayat Hidayat; Deni Fardiansyah Putra (Jurnal Pertanian Terpadu, 2026)
The development of superior agricultural commodities from a digital marketing perspective in Sumenep Regency is important to do. The industrial revolution 4.0 towards the era of society 5.0 forces various products or services to implement internet-based systems to reach wider consumers. The purpose of this study is to identify the media used and involved in the development of superior agricultural commodities in Ganding District, and what are the steps for developing sustainable superior agricultural commodities in Ganding District. The method in this study uses a qualitative case study method. The qualitative case study method attempts to provide an in-depth description of the development of superior agricultural commodities from a digital marketing perspective. The results of the study show that digital marketing has a significant role in increasing the selling price of superior agricultural commodities, especially tobacco as a superior agricultural product in Ganding District that is able to reach the market. It can be concluded that the development of superior agricultural commodities in Ganding District through a digital marketing perspective is a strategic step taken by farmers to increase the competitiveness of agricultural commodity products such as rice, corn and tobacco in a wider market so that it is easier for buyers to recognize and know the quality produced.